2012
DOI: 10.3390/molecules17033461
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Irbesartan and Hydrochlorothiazide: An Improved HPLC Method with the Aid of a Chemometric Protocol

Abstract: Experimental design method was used for HPLC determination of irbesartan and hydrochlorothiazide in combined dosage forms. The traditional approach for optimization of experiments is time-consuming, involves a large number of runs and does not allow establishing the multiple interacting parameters. The main advantages of the experimental design method include the simultaneous screening of a larger number of factors affecting response and the estimation of possible interactions. On the basis of preliminary expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…In CZE, the buffer type, pH, and concentration is a key strategy for optimizing the separation of ionizable analytes as it determines the degree of the analyte ionization, its electrophoretic mobility, and the magnitude of EOF. As ALS has a p K a value of 9.49 , AML has a p K a value of 8.7 , and HCZ has a p K a value 9.09 , ALS and AML are positively charged under acidic conditions and can be analyzed and separated from the unionized HCZ by CZE. Several running buffers such as phosphate, acetate, and borate at different pH values and molarities were tested for CZE analysis and the best results were obtained in phosphate buffer taking into consideration different parameters (migration time, resolution, peak shape, height, baseline noise, and the electric current produced).…”
Section: Resultsmentioning
confidence: 99%
“…In CZE, the buffer type, pH, and concentration is a key strategy for optimizing the separation of ionizable analytes as it determines the degree of the analyte ionization, its electrophoretic mobility, and the magnitude of EOF. As ALS has a p K a value of 9.49 , AML has a p K a value of 8.7 , and HCZ has a p K a value 9.09 , ALS and AML are positively charged under acidic conditions and can be analyzed and separated from the unionized HCZ by CZE. Several running buffers such as phosphate, acetate, and borate at different pH values and molarities were tested for CZE analysis and the best results were obtained in phosphate buffer taking into consideration different parameters (migration time, resolution, peak shape, height, baseline noise, and the electric current produced).…”
Section: Resultsmentioning
confidence: 99%
“…Few methods have been described for the determination of irbesartan in pharmaceutical dosage forms by HPLC [28][29][30][31][32], extractive spectrophotometry with Picric acid, bromocresol green, bromothymol blue, cobalt thiocyanate and molybdenum (V) thiocyanate [33], spectrophotometry [34][35][36] and HPTLC [37]. Several HPLC [38][39][40][41][42][43][44][45], spectrophotometry [44][45][46][47][48][49][50] and capillary electrophoresis methods [51,52] are reported in the literature for the determination of irbesartan in combined pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature survey was carried out and found that there are few analytical methods for the determination of hydrochlorothiazide alone or in its combination with other drugs in pharmaceutical preparations including spectrophotometry [3,4], flow injection [5], TLC [6], and HPLC [7][8][9]. A recent study involved a review of developing methods using these analytical techniques for estimation of hydrochlorothiazide in various biological samples with focus on sample pretreatment methods and separation methods [10].…”
Section: Introductionmentioning
confidence: 99%